Redox-activated protein kinase A Type I (PKA RI) exerts a protective role during pathological pressure overload. (25th November 2020) - Tarnowski, D; Islam, M.M.T; Trum, M; Eaton, P; Maier, L.S; Wagner, S; Sag, C.M
Abstract: Background: Phosphorylation of L-type calcium channels (LTCC) by cAMP-dependent protein kinase A (PKA) increases calcium current (ICa). However, it is unclear if PKA-dependent regulation of ICa is impaired in heart failure (HF) despite evidence for impaired β-adrenergic signaling. Recently, a novel PKA activation pathway by oxidation of regulatory subunit I (RI) has been identified. Objective: We investigated the impact of redox-activated PKA for regulation of ICa, intracellular calcium (Ca) handling and contractile function in a pressure overload heart failure mouse model. Methods: Knock-in mice (KI) that lack redox-dependent PKA activation (exchange of cysteine 17 of RI with serine) were compared to wild-type (WT) at baseline, 7 days and 6 weeks after transverse aortic constriction (TAC). Mouse echocardiography was performed to evaluate in-vivo cardiac function. ICa was measured by whole-cell patch clamp, PKA activity, cAMP levels, and protein levels of central Ca handling proteins were assessed at different time points in vitro. Results: At baseline, no alterations of left ventricular (LV) function (echocardiography) were observed between WT and KI. TAC induced a significant RI oxidation in WT but not KI mice. Despite this difference, at 7 days after TAC, development of LV hypertrophy and impairment of systolic LV function in vivo were similar between WT and KI. Compared to baseline, 7 days after TAC a significant stimulation of peak ICa was observed in WT. In contrast to WT, the stimulation of peak ICa was absent in KI mice at 7 days after TAC. This impairment in peak ICa occurred despite a comparable increase in global PKA activity (ELISA), which was most likely due to increased cAMP levels in our TAC model (assessed by FLIM-FRET). Notably, cAMP levels were comparably increased in between groups (ELISA). Importantly, at 6 weeks after TAC, WT mice showed a mild additional deterioration of systolic LV function in vivo. In contrast, LV function was significantly more impaired in KI mice 6 weeks after TAC, which was accompanied by a significant increase in KI mice mortality. Comparing 6 weeks to 7 days after TAC, there was no stimulation of peak ICa in WT and even a significant decrease in peak ICa in KI mice. In accordance, PKA-dependent LTCC phosphorylation was absent in KI mice 6 weeks after TAC (western blotting). Conclusion: Redox-activated PKA seems to exert a protective role by stimulation of ICa during pressure overload. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Deutsche Forschungsgemeinschaft